The Effect of Agricultural Development Project (ADP) on the Rural Farmers in Adamawa State, Nigeria - Madu , Umar Adamu; Wakili , Abba Mohammed (Asian Journal of Agriculture and Rural Development, 2012)
Majority of communities in Nigeria are rural dwellers and agrarian by occupation. Development strategy for a country whose rural population are mainly farmers cannot be achieved without first sustained growth in rural income and standard of living primarily from agriculture. It was based on this that the state wide Agricultural Development Project (ADP) was established to raise productivity, income and standard of living of rural farmers in Nigeria. This study assesses the effect of the ADP activities on the wellbeing of the rural farmers in Adamawa State, Nigeria. Data for this study were collect on annual crop output, annual income, farm size, use of improved technology, access to credit among farmers, farmers’ training and rural infrastructure development. The data were sourced using structured questionnaire and personal interviews. The statistical analysis used to determine the effect to the project on the participating farmers include, descriptive statistics and comparability test for difference (T-test) analysis. The results indicates that Adamawa ADP had positive and significant impact on rural farmers productivity, income, access to credit, standard of living as measured by assets ownership. However, the project did not have significant impact on the rural infrastructure, adoption of improved technologies and farm sizes, even though the change from before and after ADP activities was positive. The study recommends that much attention should be paid to the provision of rural infrastructure and the needed improved technologies. The study also recommends that the two tiers of government in Nigeria should adequately fund the project to efficiently cope with its responsibility of developing the rural sector.